Anti-Diarrheal Activity of the Aqueous Leaf Extract of Ageratum Conyzoides in Wistar Rats - JOT Emudainohwo; EO Erhirhie; EG Moke (Journal of Applied Sciences and Environmental Management, 2015)
The leaves of Ageratum conyzoides had been reportedly used in traditional medicine in the treatment of diarrhea. Thus its aqueous leaf extract was investigated for its possible anti-diarrheal property using castor oil induced diarrheal, charcoal meal intestinal transit and castor oil-induced enteropooling models in Wistar rats to substantiate its folklore claim. In castor oil induced diarrheal model, 500 mg/kg and 1000 mg/kg body weight doses of the extract showed dose dependent remarkable anti-diarrheal activity evidenced by delay in diarrheal latency, reduction in the rate of defecation and consistency, although it was not comparable to that loperamide which elicited absent of diarrheal. In charcoal meal intestinal transit models, extract doses (500 mg/kg and 1000 mg/kg) also elicited dose dependent anti-diarrheal activity, evidenced by reduction in distance travelled by charcoal meal. Although, it was not also comparable to that of intraperitoneal injection of standard drug, Atropine sulphate at a dose of 0.1 mg/kg body weight. Experimental findings showed that aqueous leaf extract of Ageratum conyzoides possess anti-diarrheal activity and may be a potential source of anti-diarrheal drug in future. Higher doses may possess better anti-diarrhoeal properties.